Проблема обгрунтованості моральних засад суспільства як нормативних чинників цивільного права України - Кройтор, В. А.; Kroytor, V. A.; ORCID: http://orcid.org/0000-0002-1849-5721 (Вісник КНУ імені Тараса Шевченка. Серія: Юридичні науки. - 2019. - № 3(110). - С. 16-20, 2019)
Розглянуто проблему науково-практичної обґрунтованості застосування моральних засад суспільства як нормативних чинників цивільного права України. Наголошено на недоцільність застосування положень моралі як нормативних чинників для впорядкування цивільних правовідносин. Не заперечується застосування положень моралі для впорядкування відносин, що не охоплюються предметом цивільного права. Проведено співвідношення змісту таких принципів цивільного права, як справедливість, добросовісність та розумність, з однієї сторони, і моральних засад суспільства, з іншої.

The article studies the issue of scientific and practical validity of applying ethical principles of society as regulatory factors of civil law of Ukraine. Taking into account the lack of validity of ethical principles of society as regulatory factors, the author attempts to make a correlation between the content of such principles of civil law as fairness, integrity and reasonableness, on the one hand, and ethical principles of the society, on the other hand. The author of the paper proves that it is inappropriate to apply the provisions of morality as regulatory factors for the regulation of civil relations. The conclusion on the objection to the civil regularity of ethical principles of society is based on several theses. Firstly, moral rules are not formalized, which creates a threat of arbitrary interpretation of their content. Secondly, ethical principles do not have a definite source of origin. Thirdly, the fundamental ethical rules have already been taken into account in the content of the principles of fairness, integrity and reason, which in turn create competition between the two types of regulatory factors. Unreasonable duplication of regulatory requirements reduces the functionality of the law, complicates the perception of its requirements. The competition between the principles of law and the ethical principles of society must be eliminated by refusing to give the latter the function of regulatory factors. The author of the paper does not deny the possibility of taking into account the ethical principles of society while regulating the relations that have been neglected by the "official law".

Рассмотрена проблема научно-практической обоснованности применения моральных устоев общества как нормативных факторов гражданского права Украины. Отмечено нецелесообразность применения положений морали как нормативных факторов для упорядочения гражданских правоотношений. Не оспаривается применение морали для упорядочения отношений, не охватываемых предметом гражданского права. Проведено соотношение содержания таких принципов гражданского права, как справедливость, добросовестность и разумность, с одной стороны, и моральных устоев общества, с другой.
Ethical principles of society as regulatory factors of civil law of Ukraine: the issue of validity
Кройтор, В. Проблема обгрунтованості моральних засад суспільства як нормативних чинників цивільного права України / В. Кройтор // Вісник КНУ імені Тараса Шевченка. Серія: Юридичні науки. - 2019. - № 3(110). - С. 16-20. - DOI: https://doi.org/10.17721/1728-2195/2019/3.110-3.
Keywords: Цивільне право. Civil Law. Гражданское право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; моральні засади суспільства; moral foundations of society; моральные устои общества; принципи цивільного права; principles of civil law; принципы гражданского права; нормативні чинники цивільного права; regulatory factors of civil law; нормативные факторы гражданского права; цивільно-правове регулювання; civil law regulation; гражданско-правовое регулирование